2015
DOI: 10.7763/ijssh.2015.v5.440
|View full text |Cite
|
Sign up to set email alerts
|

Developing Critical Thinking through Activity –Based and Cooperative Learning Approach in Teaching High School Chemistry

Abstract: Abstract-The study aimed to develop critical thinking in chemistry using the Third International Mathematics and Science Survey Questionnaire (TIMSS-Like Test Items) and to lessen or eradicate misconception of students in the scientific concepts. A total of 99 third year Muslim students were selected and grouped into experimental and control group based on their respective section assignment. The experimental group underwent treatment using activity-based learning in a cooperative learning environment, while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 1 publication
1
6
0
2
Order By: Relevance
“…Both groups, however, made significant gains; however, indicating the grouping did not have a significant impact on the difference in posttest scores for the two groups. This finding supports the majority of research on cooperative learning being a viable teaching strategy (Baer, 2003; Igel & Urquhart, 2012; Smith et al., 2014; Valdez et al., 2015; Vega & Hederich, 2015; Zakaria et al., 2013; Zamani, 2016). This research, however, contradicts the findings from Baer (2003),Van der Smith and Spindle (2007), and Zamani (2016) that all found that grouping techniques did make a significant impact on student achievement.…”
Section: Resultssupporting
confidence: 80%
“…Both groups, however, made significant gains; however, indicating the grouping did not have a significant impact on the difference in posttest scores for the two groups. This finding supports the majority of research on cooperative learning being a viable teaching strategy (Baer, 2003; Igel & Urquhart, 2012; Smith et al., 2014; Valdez et al., 2015; Vega & Hederich, 2015; Zakaria et al., 2013; Zamani, 2016). This research, however, contradicts the findings from Baer (2003),Van der Smith and Spindle (2007), and Zamani (2016) that all found that grouping techniques did make a significant impact on student achievement.…”
Section: Resultssupporting
confidence: 80%
“…The students acquired inductive/deductive reasoning skills, analyzed, synthesized, rated information, and interpreted during the problem-solving process. In line with this, Valdez et al (2015) also concluded in his research that learning by constructing previous knowledge experiences, exploratively, and interactively could develop students' critical thinking skills.…”
Section: Psychomotor Domainmentioning
confidence: 69%
“…Hal ini diperkuat oleh penelitian sebelumnya yang mengembangkan keterampilan berpikir kritis dan kreatif dengan pembelajaran yang terfokus pada mahasiswa. Valdez et al, (2015) menyatakan bahwa pembelajaran kooperatif dan berbasis aktivitas pada pembelajaran kimia mampu meningkatkan keterampilan berpikir kritis. Sementara itu, Yoon et al, (2014) menyatakan bahwa pembelajaran berbasis masalah pada topik penanganan terhadap air yang terkontaminasi asam basa mampu meningkatkan keterampilan berpikir kreatif mahasiswa.…”
Section: Hasil Dan Pembahasanunclassified